Excellent Healing after Severe Lid Injury by a Bird: Doi: 10.36351/pjo.v37i4.1281 - Chaudhry, Tanveer; Shamim, Nida (Pakistan Journal of Ophthalmology, 2021)
Eye lid lacerations secondary to penetrating trauma is quite common. Most of the injuries occur due to animal bites, falls and collision with sharp objects. They may lead to partial or full thickness lid defects. We report a case of middle aged woman who was attacked by bird claws and sustained severe upper lid laceration that was immediately thoroughly investigated and then managed surgically resulting in excellent wound healing. Ocular trauma from bird pecking injury can cause blindness in humans. The public should guard against feeding and keeping close with them. If immediate medical attention is given by the ophthalmologist and urgent primary repair is done there are high chances to save the eye from disastrous complications. Key Words: Lid laceration, ocular trauma, penetrating injury.